1959
DOI: 10.1103/physrev.114.1037
|View full text |Cite
|
Sign up to set email alerts
|

Cross Sections for theLi7(n, γ)Li8Reaction

Abstract: 1037the only negative ion which has been identified in HC1 by previous workers is Cl~. Charge transfer would not be expected to play a significant role if this were the ion in our experiment. The observed value of 0.71 ±0.02 cm 2 /v-sec is to be contrasted with that of 0.88 expected if Eq. (14) is applicable. This suggests that an orientation-dependent R~* interaction is important in this case, so that the mobility should vary as T 1/6 . If, however, these forces averaged out, so that only the INTRODUCTION R A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
3
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 14 publications
7
96
3
3
Order By: Relevance
“…Of course there were old data which were consistent with the theoretical prediction: these [12] were 59G11.8 and 39.5G7.9 mb. In these circumstances, our result [3] was 39.8G6.0 mb: the puzzle was solved.…”
Section: Conditions Of Neutron Capture Nucleosynthesessupporting
confidence: 68%
See 1 more Smart Citation
“…Of course there were old data which were consistent with the theoretical prediction: these [12] were 59G11.8 and 39.5G7.9 mb. In these circumstances, our result [3] was 39.8G6.0 mb: the puzzle was solved.…”
Section: Conditions Of Neutron Capture Nucleosynthesessupporting
confidence: 68%
“…Finally, the capture cross sections of the objective nucleus were derived from the capture yields, the neutron data obtained with the 6 Li-glass detector, and the standard capture cross sections of 197 Au. 12 C, there were two experimental data previously: 200G400 mb at 30 keV by Gibbons et al [5] and an upper limit of 14 mb at 30 keV by Macklin [6]. On the other hand, an extrapolation with the 1/v law [7] and the capture cross section [8] at the thermal energy (0.025 eV) gave about 3 mb at 30 keV, where v is the velocity of incident neutron in the center of mass system.…”
Section: Conditions Of Neutron Capture Nucleosynthesesmentioning
confidence: 99%
“…energies (up to 1 MeV) [20][21][22][23]. Only the 3 + state at 2.25 MeV (0.22 MeV above the neutron decay threshold) has been observed.…”
Section: New States In Light Of Previous Experimental Datamentioning
confidence: 97%
“…Measurements by Wiescher et al (1989) had indicated that the cross section for this reaction was a factor of 2 smaller than reported by Imhof et al (1959), thereby reducing the rate of heavy element synthesis in any primordial r process. However, a number of more recent measurements (Blackmon et al, 1996, and references therein) are in good agreement with the Imhof (1959) results supporting the reaction rate used in the calculation of heavy element production by Malaney and Fowler (1987). It is perhaps interesting to note that the three-cluster generator coordinate method calculations of Descouvemont and Baye (1994), which are consistent with the Imhof/Blackmon 7 Li(n,␥) 8 Li results, predict S 17 (0)у24 eV b for the isospin mirror, 7 Be(p,␥) 8 B reaction.…”
Section: Hydrogen Burning In the Pp Chain And Cn Cyclementioning
confidence: 99%